Synthesis of Diversely Substituted Diethyl (Pyrrolidin-2-Yl)Phosphonates - Andrea Bagán; Alba López-Ruiz; Sònia Abás; Elies Molins; Belén Pérez; Itziar Muneta-Arrate; Luis F. Callado; Carmen Escolano (Molecules)
Imidazoline I2 receptors (I2-IR) are untapped therapeutic targets lacking a structural description. Although the levels of I2-IR are dysregulated in a plethora of illnesses, the arsenal of ligands that can modulate I2-IR is limited. In this framework, we have reported several new structural families embodying the iminophosphonate functional group that have an excellent affinity and selectivity for I2-IR, and selected members have demonstrated relevant pharmacological properties in murine models of neurodegeneration and Alzheimer’s disease. Starting with these iminophosphonates, we continued to exploit their high degree of functionalization through a short and efficient synthesis to access unprecedented 2,3-di, 2,2,3-tri, 2,3,4-tri, and 2,2,3,4-tetrasubstituted diethyl (pyrrolidine-2-yl) phosphonates. The stereochemistry of the new compounds was unequivocally characterized by X-ray crystallographic analyses. Two selected compounds with structural features shared with the starting products were pharmacologically evaluated, allowing us to deduce the required key structural motifs for biologically active aminophosphonate derivatives.